Pathogenicity of Fusarium oxysporum f. sp. nicotinae and F. phyllophilum in tobacco in the Granma region, Cuba - Holguín-Peña, Ramon; Ruiz-Juárez, Daniel; Gutiérrez-Rojas, Mónica; Ceiro-Catasú, Wilson (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
Diseases caused by Fusarium spp. are considered cosmopolitan and affect a great diversity of crops worldwide. In the tobacco-growing areas of Granma province, located in eastern Cuba, these phytopathological problems cause significant losses in tobacco leaf yield and quality. To address this critical issue, a comprehensive study was conducted, focusing on disease monitoring and the identification of tobacco seeds and seedlings (cv. Corojo 2012) affected by the diseases. The study also examined the variables associated with the severity of the diseases. The results of the study indicated that the vascular wilt was caused by two distinct fungal pathogens: F. oxysporum f. sp. nicotinae and F. phyllophilum. The study revealed that the disease exhibited levels of recurrence in both space and time, reaching up to 62 % necrosis in seedlings with no chance of survival. This disease severity, measured on a maximum scale of five, attained a maximum score of 4.20. The findings indicated a substantial inhibition in the germination and growth variables of Nicotiana tabacum, which has a profound impact on the yield and commercial quality of N. tabacum leaves, particularly those intended for the Cuban cigar manufacturing industry. This underscores the necessity for expeditious diagnosis of the disease and the implementation of appropriate management strategies to mitigate the risks of its propagation in producing regions of Cuba and globally.